2019
DOI: 10.1177/0091415019868227
|View full text |Cite
|
Sign up to set email alerts
|

Retirement, Pensions, and Depressive Symptoms Among Older Adults in China, England, Mexico, and the United States

Abstract: This study explores the associations of retirement, and of public and private pensions, with older adults’ depressive symptoms by comparing differences between countries and age groups. Harmonized data were analyzed from the family of Health and Retirement Study in 2012–2013 from China, England, Mexico, and the United States ( n =  97,978). Respondents were asked if they were retired and received public or private pensions. Depressive symptom was measured by the Center for Epidemiologic Studies Depression Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
(95 reference statements)
1
13
1
2
Order By: Relevance
“…In the multivariate latent growth curve models (described below), we controlled for a number of variables that previous research has shown can influence peoples' well-being and adjustment to retirement (cf. Barbosa et al 2016;Lu and Shelley 2019;Nyberg et al 2019). Age, sex, years of education, civil status (coded as 1 = married/partner, 0 = not married or partner), income satisfaction, leisure activities, and self-rated health were included as control variables.…”
Section: Control Variablesmentioning
confidence: 99%
“…In the multivariate latent growth curve models (described below), we controlled for a number of variables that previous research has shown can influence peoples' well-being and adjustment to retirement (cf. Barbosa et al 2016;Lu and Shelley 2019;Nyberg et al 2019). Age, sex, years of education, civil status (coded as 1 = married/partner, 0 = not married or partner), income satisfaction, leisure activities, and self-rated health were included as control variables.…”
Section: Control Variablesmentioning
confidence: 99%
“…For example, retirement (with a pension) was found to have a protective association for depression when comparing to a working population [ 16 ]; however, the association differed between different contexts. Retirement has been found to be associated with higher depressive symptoms in the United States, and with lower depressive symptoms in Mexico and England [ 17 ], also suggesting contextual differences. There are older adults who experience ambivalence, anxiety, fear, and a feeling of loss, when they retire [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, different from the Chinese society before the reform and opening up, since the reform and opening up in 1978, the Chinese government has gradually established a modern social security system. For older population, high occupational status also means higher pension and more stable welfare security, which will promote their mental health after retirement [ 34 ]. Therefore, this study proposes the following hypothesis.…”
Section: Introductionmentioning
confidence: 99%